Targeting carbonic anhydrase IX and XII isoforms with small molecule inhibitors and monoclonal antibodies - Mateusz Kciuk; Adrianna Gielecińska; Somdutt Mujwar; Mariusz Mojzych; Beata Marciniak; Rafał Drozda; Renata Kontek (Taylor & Francis Group, 2022)
Carbonic anhydrases IX and CAXII (CAIX/CAXII) are transmembrane zinc metalloproteins that catalyze a very basic but crucial physiological reaction: the conversion of carbon dioxide into bicarbonate with a release of the proton. CA, especially CAIX and CAXII isoforms gained the attention of many researchers interested in anticancer drug design due to pivotal functions of enzymes in the cancer cell metastasis and response to hypoxia, and their expression restricted to malignant cells. This offers an opportunity to develop new targeted therapies with fewer side effects. Continuous efforts led to the discovery of a series of diverse compounds with the most abundant sulphonamide derivatives. Here we review current knowledge considering small molecule and antibody-based targeting of CAIX/CAXII in cancer.